Tuberculous Osteomyelitis of Parietal Bone in a Child: A Case Report with Brief Literature Review - Karki, Mohan (Nepal Journal of Neuroscience, 2025)
Tuberculous osteomyelitis of skull is a rare entity. It is also reported in healthy person without any evidence of tuberculosis elsewhere in the body, therefore diagnosis is not suspected. However, we rarely come across tuberculous osteomyelitis of right frontal bone following trauma. We present a case of left parietal tuberculous osteomyelitis who presented with headache, scalp swelling and discharging pus from over left parietal scalp region following trauma. Patient was managed by excision of lesion with diseased bone and mesh cranioplasty, and ant-tubercular therapy. Diagnosis of tuberculous osteomyelitis was made on the basis of histopathology report of biopsy specimen.